2019
DOI: 10.1016/j.ejor.2019.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Delay-time modelling of a critical system subject to random inspections

Abstract: We model the inspection-maintenance of a critical system in which the execution of inspections is random. The models we develop are interesting because they mimic realities in which production is prioritised over maintenance, so that inspections might be impeded or they might be opportunistic. Random maintenance has been modelled by others but there is little in the literature that relates to inspection of a critical system. We suppose that the critical system can be good, defective or failed, and that failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…When an external shock comes, one of two types of shock is incurred according to its effectiveness, that is, Type I shock with a time‐dependent probability p ( t ) (0 ≤ p ( t ) ≤ 1), which increases system degradation level; and Type II shock with a probability q ( t ), which results in a traumatic failure, where p ( t )+ q ( t ) ≡ 1. Most of Type I shocks are avoided owing to the fault tolerant design that is analyzed by the generalized m − δ shock model proposed in Liu et al 30 The system is regarded as failure when the total degradation amount caused by both natural degradation and Type I shock reaches a prescribed threshold or when a Type II shock occurs for the first time, whichever takes place first. In the following contents, the different failure modes are modeled respectively in more details, highlighting the dependence between the traumatic failure and the degradation failure.…”
Section: System Reliability Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…When an external shock comes, one of two types of shock is incurred according to its effectiveness, that is, Type I shock with a time‐dependent probability p ( t ) (0 ≤ p ( t ) ≤ 1), which increases system degradation level; and Type II shock with a probability q ( t ), which results in a traumatic failure, where p ( t )+ q ( t ) ≡ 1. Most of Type I shocks are avoided owing to the fault tolerant design that is analyzed by the generalized m − δ shock model proposed in Liu et al 30 The system is regarded as failure when the total degradation amount caused by both natural degradation and Type I shock reaches a prescribed threshold or when a Type II shock occurs for the first time, whichever takes place first. In the following contents, the different failure modes are modeled respectively in more details, highlighting the dependence between the traumatic failure and the degradation failure.…”
Section: System Reliability Modellingmentioning
confidence: 99%
“…29 Fault tolerance, which is often achieved by some kinds of self-constrained redundancies, is targeted at the development of a system that functions correctly in presence of faults and is most commonly used in computer systems. 30 For example, an onboard error detection and correction (EDAC) device is usually incorporated in memory chips operated in space radiation environments to detect and correct upset errors. This fault tolerant ability is constrained to central process unit (CPU) and random access memory resources, enabling the memory chip to continue more or less its intended operation, possibly at a reduced level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we developed an optimization model based on a delay time model from the reliability and machine maintenance literature to capture disease-monitoring dynamics. The delay-time model is widely applied to model engineering problems in machine maintenance and inspection; it assumes that a device's life cycle has an increasing failure rate [35][36][37]. The period that starts with the device showing signs of failure, and ending with the final failure, is called the delay time.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [33] developed a two-phase PM model, where preventive replacement in the second phase is delayed to sufficiently utilize the system's remaining lifetime and facilitate replacement preparations. Scarf et al [34] found that for a critical system, opportunistic inspections may offer an economic advantage against periodic inspections in certain cases. On the other hand, the working cycle of a system that executes successive jobs, might be variable.…”
Section: Introductionmentioning
confidence: 99%